Safety of natural mixture of illite, montmorillonite and kaolinite (Argile Verte du Velay) for all animal species. (24th July 2018) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive is a natural mixture mainly composed of illite ( 53%), montmorillonite ( 16%) and kaolinite ( 17%), referred as MIMK. In 2016 and in 2017, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) delivered two opinions on the safety and efficacy of the additive. In these opinions, the Panel concluded that the additive is safe for piglets, pigs for fattening and cattle for fattening and minor growing ruminants at a maximum concentration of 50, 000 mg/kg. No conclusions could be drawn on the safety for poultry or any other species/categories. Following these opinions, the European Commission gave the possibility to the applicant to submit complementary information in order to complete the assessment on the safety for all animal species. The applicant submitted a new tolerance study with chickens for fattening showing no adverse effect of the additive MIMK up to 100, 000 mg/kg complete feed (twofold the highest recommended use level). The FEEDAP Panel therefore concludes that 50, 000 mg MIMK/kg complete feed is safe for chickens for fattening. MIMK was already considered safe, at the same dietary concentration, for cattle for fattening with a margin of safety of two and for piglets but without a margin of safety. Therefore, extrapolation to all animal species is not possible for the concentration of 50, 000 mg MIMK/kg complete feed. The Panel notes that the concentration of 20, 000 mg MIMK/kg feed was tested in all the tolerance studies assessed and shown to be safe, with a margin of safety of at least 2.5. The Panel concludes that the additive MIMK is safe at 50, 000 mg/kg complete feed for chickens for fattening and minor growing poultry species, for cattle for fattening and minor growing ruminant species and growing pigs; and at 20, 000 mg/kg complete feed for all other animal species and categories.